TINJAUAN YURIDIS TERHADAP ALOKASI DESA DI KECAMATAN TABANG YANG TIDAK SESUAI DENGAN PROGRAM PEMERINTAH KABUPATEN KUTAI KARTANEGARA - Supardi Supardi (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
ABSTRACTThe purpose of this study is to provide an overview of the implementation of the Village Fund Allocation in the village of barusub district tabang kutai regency as well as contributing factor and obstacles affecting the implementation and strategies that must be done in order of success programs government but it also will provide recommendations to the local government in the management of the village fund allocation.The method used in this research is qualitative descriptive method, where the main instrument in the study is the researchers themselves. Sources of date used is the source of primary data and secondary data relating to the circumenstances of government programs. In this study, the authors also use the survey in order to obtain primary data on the village fund allocation policy in new village district of tabang regency. On the basis of available data, the authors attempt to describe/ illustrate a systemtic, factual and accurate information on the facts, characteristic and relationship between phenomena that exist. The results showed that the implementation of the policy of the village fund allocation (ADD) in the village of barusud district tabang kutai regency went pretty smoothly. However, when linked whit the government programmes, the implementationof the village fund allocation (ADD) in new village district of kutai regency tabang not optimal. Although the purpose of improvement of government and community development, has been implemented optimally, but the purpose of the upgrading of an association of villages in the planning, implementation and control of the development has not run optimally. Likewise, the purpose of increasing the participation of non-governmental mutual aid society is not optimal.Some of the factors that affect the implementation of the programmes government in managing the village fund allocation (ADD) in the village of barusub distric tabang kutai regency is comumunication, human resource capabilities, attitudes executor, buresucratic structure, the environment and the size and purpose of the policy is not appropriate.